COMPARISON OF CARDIOVASCULAR EVENTS AMONG USERS OF DIFFERENT CLASSES OF ANTI-OSTEOPOROSIS MEDICATIONS - Chen, Weiche; Tsai, WenHsuan; Tsai, MingJie (Journal of the ASEAN Federation of Endocrine Societies, 2022)
OBJECTIVES Anti-osteoporosis medications have been associated with the occurrence of cardiovascular events. Therefore, we aimed to investigate the cardiovascular safety of hormone replacement therapy (HRT), bisphosphonates, anti-RANKL, parathyroid hormone (PTH) analogues and romosozumab in patients with osteoporosis. METHODOLOGY We evaluated 77 trials including 106,982 patients comparing five classes of anti-osteoporosis drugs and a placebo. We initially performed a standard, random-effect, pairwise meta-analysis for cardiovascular disease (CVD) risk to gather the available direct evidence of each drug class. For every possible pairwise comparison, the association between treatment and outcomes was obtained using odds ratios (ORs). Statistical heterogeneity was assessed along with its 95% confidence intervals. Network meta-analysis was then used to compare different available treatment strategies within a single analytical framework in a Bayesian setting. RESULTS Patients on hormone therapy, bisphosphonates, romosozumab and PTH had no increased cardiovascular risk compared to placebo. Anti-RANKL use revealed a significantly higher risk of CVD than placebo with a risk ratio of 1.25 [95% CI 1.07-1.45]. The SUCRA ranking confirmed that the use of anti-RANKL conferred the highest risk for CVD in patients with osteoporosis. Specifically, there was a significantly higher risk of coronary artery disease, cerebrovascular disease, angina and transient ischemic accident (RR 1.26 [95% CI 1.01-1.58]).On the other hand, HRT demonstrated a higher risk of venous thromboembolic events (VTE) (RR 1.96 [95% CI 1.53-2.51]). CONCLUSION From our network meta-analysis, the use of anti-RANKL such as denosumab increased the risk of composite cardiovascular outcomes, while HRT increased the risk of VTE.